Intra‐Seasonal Variabilities Associated With Tropical Cyclones in Eastern and Southeastern Asian Regions and Their Recent Change - Rui Jin; Johnny C. L. Chan; Hui Yu; Peng Zhang (Geophysical Research Letters)
Abstract This study focuses on the diverse intra‐seasonal variabilities (ISVs) exhibited by tropical cyclone (TC) occurrence frequency affecting southeastern and eastern Asian regions, classified as SEATOFs and EATC occurrence frequency (EATOFs). Both groups exhibit pronounced 8–20‐day variability, particularly in EATOFs, whereas SEATOFs demonstrate an additional 20–60‐day peak. The corresponding 8–20‐day atmospheric ISVs are focused on, which closely mirror the tropical quasi‐biweekly oscillation (QBWO) but differ in spatial structure. SEATOFs are tied to a zonally elongated, westward‐propagating QBWO (W‐QBWO), while EATOFs are linked to a west‐northward‐propagating QBWO (NW‐QBWO) with a slight southwest‐northeast tilt and intensified perturbations along the East Asian coast. Notably, EATOFs and their 8–20‐day ISV amplitude have concurrently increased since the late 1990s. This shift can be attributed to an interdecadal shift of QBWO dominance from W‐QBWO to NW‐QBWO. These results highlight the QBWO's substantial influence on TC activities across both Asian regions, particularly along the East Asian coast.